The 1st International Electronic Conference on Biosensors 2020
DOI: 10.3390/iecb2020-07055
|View full text |Cite
|
Sign up to set email alerts
|

2D Nanomaterial, Ti3C2 MXene-Based Sensor to Guide Lung Cancer Therapy and Management

Abstract: Major advances in cancer control can be greatly aided by early diagnosis and effective treatment in its pre-invasive state. Lung cancer (small cell and non-small cell) is a leading cause of cancer-related death among both men and women around the world. A lot of research attention has been attracted to diagnosing and treating lung cancer. A common method of lung cancer treatment is based on COX-2 (Cyclooxygenase-2) inhibitors. This is because COX-2 is commonly over expressed in lung cancer and also the abundan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Yang et al showed that 8-HOcA can be used as a histone deacetylase inhibitor (HDACi) to inhibit the growth of colon cancer cells and pancreatic cancer cells in a p53-dependent or independent manner by blocking the cell cycle in G1 and promoting cell apoptosis, which is an anticancer byproduct . Sadiq et al revealed that detecting the level of 8-HOcA in cancer cells can provide timely guidance for the treatment of lung cancer . The above research shows that 8-HOcA has good biological activity; however, studies on the mechanism of the difference in the content during honey brewing in different honey entomological origins have not been reported; therefore, the molecular mechanism of its production needs to be further investigated at the level of gene expression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yang et al showed that 8-HOcA can be used as a histone deacetylase inhibitor (HDACi) to inhibit the growth of colon cancer cells and pancreatic cancer cells in a p53-dependent or independent manner by blocking the cell cycle in G1 and promoting cell apoptosis, which is an anticancer byproduct . Sadiq et al revealed that detecting the level of 8-HOcA in cancer cells can provide timely guidance for the treatment of lung cancer . The above research shows that 8-HOcA has good biological activity; however, studies on the mechanism of the difference in the content during honey brewing in different honey entomological origins have not been reported; therefore, the molecular mechanism of its production needs to be further investigated at the level of gene expression.…”
Section: Resultsmentioning
confidence: 99%
“…35 Sadiq et al revealed that detecting the level of 8-HOcA in cancer cells can provide timely guidance for the treatment of lung cancer. 36 The above research shows that 8-HOcA has good biological activity; however, studies on the mechanism of the difference in the content during honey brewing in different honey entomological origins have not been reported; therefore, the molecular mechanism of its production needs to be further investigated at the level of gene expression.…”
Section: Determination Of Differential Compounds In a Mellifera And A...mentioning
confidence: 99%
“…In our conference paper [50], we reported that the as-synthesized Ti 3 C 2 MXene-based nanosensor has effectively detected 8-HOA in cancer cells without and with using a D5D inhibitor. In that paper, we described more details about how the new sensor based on the two-dimensional nanomaterial Ti 3 C 2 MXene [51] can facilitate the lung diagnosis and treatment efficiently by using the new D5D inhibitor and 8-HOA therapy on lung cancer. The preliminary data indicate that this new sensor device can sensitively detect PGE 2 and 8-HOA levels in healthy and cancerous lung cells (BEAS2B and A549 respectively) with similar accuracy to GC-MS but much faster and in an in-time manner to guide the cancer treatment.…”
Section: Ti3c2 Nanomaterial-based Sensor Preparationmentioning
confidence: 99%